1996
DOI: 10.1212/wnl.47.3.644
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Parkinson's disease II

Abstract: In a case-control study, we compared the past dietary habits of 342 Parkinson's disease (PD) patients recruited from nine German clinics with those of 342 controls from the same neighborhood or region. Data were gathered with a structured interview and a self-administered food-frequency questionnaire. Nutrient intakes were calculated from the reported food intakes through linkage with the German Federal Food Code and analyzed using multivariate conditional logistic regression to control for total energy intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 14 publications
6
137
3
Order By: Relevance
“…A case -control study in Germany found that a higher intake of folate, vitamin B 6 and vitamin B 12 , but not of riboflavin, was associated with a lower risk of PD (5) . A prospective cohort study in the Netherlands showed that a higher intake of vitamin B 6 , but not of folate or vitamin B 12 , was associated with a decreasing risk of PD (6) .…”
Section: Discussionmentioning
confidence: 99%
“…A case -control study in Germany found that a higher intake of folate, vitamin B 6 and vitamin B 12 , but not of riboflavin, was associated with a lower risk of PD (5) . A prospective cohort study in the Netherlands showed that a higher intake of vitamin B 6 , but not of folate or vitamin B 12 , was associated with a decreasing risk of PD (6) .…”
Section: Discussionmentioning
confidence: 99%
“…In a German casecontrol study, intake of folic acid equivalents was related to lower risk of PD (OR 0.51, 95% CI 0.26-0.99 for highest quartile versus lowest), although the corresponding trend test was nonsignificant (p for trend 0.08) [486]. A US case-control study found no associations with folate or vitamin B6 intake [489].…”
Section: Antioxidantsmentioning
confidence: 92%
“…Among case-control studies that assessed the role of macronutrients in PD (total energy intake, intake of fat, protein, and carbohydrates), two reported higher energy intake among cases than among controls [486,487] and two found no such association [488,489]. One case-control study reported lower risk with increasing glycemic index, but no associations for glycemic load or total intake of carbohydrates [490].…”
Section: Macronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies presented variable findings. Higher intake of vitamins B6, B9, and B12, but not B2, was associated with lower risk of PD in a German population [19]. Riboflavin supplementation with 8-hour intervals for 6 months gave rise to promising improvements in motor activity of patients.…”
Section: Neuroprotective Nutrients Vitaminsmentioning
confidence: 91%